DNA barcodes for pathogens of African food crops - Kumar, L.; Sharma, K. (2010)
Studies were conducted to characterize pathogen populations and recognize unique stretches of sequences, known as DNA barcodes, that can be used as genetic markers for the rapid diagnosis of the pathogens and pests affecting the African food crops. The fungal pathogen causing anthracnose (Glomerella cingulata), the most destructive disease of yam and cassava in West Africa, were characterized. Various isolates of this fungus were identified and their genetic relatedness and diversity were determined through molecular analysis. They were grouped into spot (S) and blight (B) isolates based on symptoms they induce. The genetic diversity of these isolates was assessed by nucleotide sequencing and cluster analysis of the 540 base pair (bp) nuclear ribosomal internal transcribed spacer region (ITS1, ITS2 and the 5.8S gene) and partial gene sequences of actin (240 bp) and histone (370 bp). Phylogenetic cluster analysis grouped the 25 isolates into 2 major clades and 2 subclades within the major clades. Both the S and B isolates were distributed between the 2 clades. All the isolates in clade 1 were unique to yam. Seven of these isolates formed a genetically distinct lineage, indicating that they could be new strains unique to yam. Isolates in clade 2 infected both cassava and yam, suggesting their capability to infect a wide range of plants. Unique sequence motifs were recognized and diagnostic PCR primers directly from infected plant tissues were designed for the specific amplification of G. cingulata affecting yam and cassava. Using a similar approach, the fungal agent associated with gray leaf spot (GLS), the most destructive disease of maize, was characterized. It was found that GLS in Nigeria was caused by a distinct species of Cercospora. This work allowed the establishment of a unique set of primers for the specific identification of the GLS pathogen prevalent in Nigeria. Through comparative genomics, common genome regions were identified in African cassava mosaic begomoviruses occurring in sub-Saharan Africa. A simple multiplex PCR assay was developed that can detect all the major viruses in cassava mosaic disease aetiology. This test was adopted for virus indexing of cassava propagated in vitro. To aid in the diagnostics research, a simple and cost-effective procedure suitable for extraction of DNA from seeds, leaves, stems, tubers and even roots was developed. The resultant DNA was suitable for PCR-based diagnoses of fungi, bacteria and viruses in the infected tissues of a wide range of plant species.